LEGALITAS DAN IMPLEMENTASI PUNGUTAN DESA ADAT TERHADAP PENDUDUK NONPERMANEN DI WILAYAH DESA ADAT KESIMAN - Ni Kadek Sintia Dewi; Ketut Sukawati Lanang Putra Perbawa (Jurnal Hukum Mahasiswa, 2021)
The high economic growth in Bali causes many people outside Bali to come to Bali to work. As a result of residents outside Bali coming to Bali, Bali is currently experiencing population density. One of the components of population that contributes to population density is the presence of non-permanent residents. Non-permanent residents are generally migrants in the customary village area, who come and live in the area for an interest, such as working to earn a living or other interests. Traditional Village levies to non-permanent residents living in the Kesiman Traditional Village area have strong legality, because they meet the formal and material requirements for the formation of a pararem and are in the form of levies made every month for Kesiman Traditional Village income which is used for ceremonial, religious, social, and customary activities. and protecting the environment of the Kesiman Traditional Village area, has been effective by giving legal consequences to non-permanent residents of their rights and obligations who live in the Kesiman Traditional Village area.